Keragaan Karakter Vegetatif Beberapa Varietas Kedelai (Glycine max L Meril) dengan Pemberian Abu Vulkanik Gunung Kelud - Tri Rahayuningsih; Agus Suryanto; Meiyana Hikmawati; Budi Prasetyo Nugroho (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
The purpose of this study was to determine the characteristics of several soybean varieties, primarily to identify the extent to which volcanic ash from Mount Kelud affects the growth of four soybean varieties: Argomulyo, Burangrang, Dering 1, and F2 Gumitir x MLG 0120. The research method used in this study was a Factorial Randomized Block Design with three replications, consisting of two factors. Factor I was the Use of Varieties consisting of four varieties (V), namely the Argomulyo Variety (VI), the Burangrang Variety (V2), and the Dering I Variety (V3), and F2 Gumitir x MLG 0120 (V4). Meanwhile, Factor II was the Use of Planting Media Composition consisting of three media compositions (M): compost and soil as a control with a ratio of 1:1 (M0), compost and volcanic ash and soil with a ratio of 1:1:1 (M1), and compost and volcanic ash with a ratio of 1:1 (M2). Observation parameters included: Plant Height, Number of Leaves, and Number of Branches per Plant. The research analysis used a factorial randomized block design, while for further testing, a 5% LSD test was used. The results showed that at the beginning of growth, the volcanic ash treatment and variety did not significantly affect plant height or leaf number. The Argomulyo variety (V1) tended to have lower plant height, while the Burangrang variety (V2) and the F2 Gumitir x MLG 0120 (V4) tended to have higher plant height. The F2 Gumitir x MLG 0120 (V4) tended to have lower leaf number, while the Argomulyo variety (V1) and the Dering I variety (V3) tended to have higher leaf number. All four varieties had their own advantages. The variety treatment and volcanic ash application did not significantly affect the number of branches per plant.